SPIRIT KEILMUAN WAHYU MEMANDU ILMU DALAM PENGEMBANGAN HUKUM ISLAM - Deden Najmudin (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
In the development of Islamic law that covers all aspects of people's lives, both in the hereafter problem with all its problems, as well as world problems with all these problems require a new paradigm of scientific mindset. The more advanced development of science and technology also influences the progress of social life, culture, politics, economics and others. So the authors take up this theme using descriptive and comparative methods, and the type of data used in this study is qualitative data. Islamic law requires a new paradigm of mindset and renewal of the views of a problem, especially in everyday life or we can call it contemporary fiqh. The paradigm of the new paradigm becomes more severe, due to contemporary problems, even more complicated when seen from the perspective of fiqh. However, the tradition of the fuqaha used to guide the dynamics of life in his day, so that in this day and age we can imitate the ulama fuqaha by at least contributing to the development of science and understanding, with various kinds of problems in society in accordance with the times, so that the problems of religious life the people are always guided. This paper will raise the opportunity given by Islamic law itself to its people to always criticize it, which allows the emergence of new paradigms along with the emergence of new problems in society.